2006
DOI: 10.1007/s00477-006-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-particle models for the estimation of the mean and standard deviation of concentrations in coastal waters

Abstract: In this paper we study the mean and standard deviation of concentrations using random walk models. Two-particle models that take into account the space correlation of the turbulence are introduced and some properties of the distribution of the particle concentration are studied. In order to reduce the CPU time of the calculation a new estimator based on reverse time diffusion is applied. This estimator has been recently introduced by Milstein et al. (Bernoulli 10(2):281-312, 2004). Some numerical aspects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is shown that this forward-reverse density estimator (FRE) is basically root-N consistent in any dimension, this in contrast to the Parzen-Rosenblatt estimator which has accuracy N −1/(4+d) for dimension d. The forward-reverse estimator has turned out to be very useful for many practical applications. For example, in van den Berg, Heemink, Lin, Schoenmakers [1], Spivakovskaya, Heemink, Milstein, Schoenmakers [20], and Spivakovskaya, Heemink, Schoenmakers [21], the FRE is applied successfully to the estimation of pollutant concentrations in small coastal water regions, which are caused by a certain calamity at another place. In the latter applications the pollutants are modelled by a diffusion process.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that this forward-reverse density estimator (FRE) is basically root-N consistent in any dimension, this in contrast to the Parzen-Rosenblatt estimator which has accuracy N −1/(4+d) for dimension d. The forward-reverse estimator has turned out to be very useful for many practical applications. For example, in van den Berg, Heemink, Lin, Schoenmakers [1], Spivakovskaya, Heemink, Milstein, Schoenmakers [20], and Spivakovskaya, Heemink, Schoenmakers [21], the FRE is applied successfully to the estimation of pollutant concentrations in small coastal water regions, which are caused by a certain calamity at another place. In the latter applications the pollutants are modelled by a diffusion process.…”
Section: Introductionmentioning
confidence: 99%
“…However, by studying the process conditioned on starting in A and ending in B, one can efficiently observe on which paths the configuration typically travels from A to B. Other possible applications appear in the field of stochastic environmental models, for instance, regarding the concentration evolutions of pollution in water; for example see Spivakovskaya, Heemink and Schoenmakers (2007) and references therein for a related problem. Several approaches for simulation of diffusion bridges have already been studied in the literature.…”
mentioning
confidence: 99%